1988
DOI: 10.1093/carcin/9.12.2309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA damage in the oral mucosa of tobacco users and non-users by 32P-adduct assay

Abstract: Tobacco and its combustion products contain several known or potential human carcinogens and studies are now beginning to emerge for detecting DNA and protein adducts in tobacco users. A highly sensitive 32P-adduct assay, capable of measuring a wide spectra of aromatic and/or hydrophobic DNA adducts, was used to evaluate tobacco use-related adducts in human oral mucosal cells. Two volunteer groups of people participated: one, a random group of cigarette smokers (n = 28) with non-smoker controls (n = 13) from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…One of the adducts was at higher levels in some of the exposed groups, while two adducts were at reduced levels. Another study of tobacco smokers, tobacco chewers, and tobacco non-users found low levels of DNA adducts in oral mucosal cells from all three groups using the butanol extraction procedure of the 32P-postlabeling assay (27). None of the adducts detected were found to be specifically associated with tobacco smoking or chewing.…”
Section: Smoking-related Dna Adducts In Human Tissuesmentioning
confidence: 98%
“…One of the adducts was at higher levels in some of the exposed groups, while two adducts were at reduced levels. Another study of tobacco smokers, tobacco chewers, and tobacco non-users found low levels of DNA adducts in oral mucosal cells from all three groups using the butanol extraction procedure of the 32P-postlabeling assay (27). None of the adducts detected were found to be specifically associated with tobacco smoking or chewing.…”
Section: Smoking-related Dna Adducts In Human Tissuesmentioning
confidence: 98%
“…This extra step extended the detection limit to a single adduct in 10 9 –10 10 nucleotides while maintaining the extremely low sample requirements of only 1–10 μg of DNA [19]. In 1986, Reddy and Randerath [20] used Nuclease P1 enrichment to achieve similar sensitivity and in 1988 [21], reversed-phase high performance liquid chromatography (HPLC) was used for the separation of unadducted from adducted nucleotides, as well as for separation of adducts with different structures into individual fractions which were then visualized on TLC plates, significantly diminishing the detection complexity. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…3 shows data comparing butanol and nuclease P1 enrichment in conjuction with 32 P-postlabeling in a study of DNA adducts from tobacco chewers [1,21]. In this case, butanol enrichment was proven to be superior to nuclease P1 enrichment in the isolation of adducts from oral mucosa [1,21]. While nuclease P1 treatment works well with PAH adducts, it does not work well with aromatic amines or C8-dG adducts [2224].…”
Section: Methodsmentioning
confidence: 99%
“…Initial reports on dosimetry of DNA adducts in the oral mucosa cells were inconclusive both in smokers versus non-smokers and in di erent groups of tobacco users, such as betel nut chewers, Khaini tobacco chewers and inverted smokers (Dunn andStich 1986, Chacko andGupta 1988). Subsequently, NP1-and butanol-enhanced 32 P-postlabelling analyses showed a higher level of adducts in the oral mucosa cells of smokers and suggested the aromatic amines and/or nitroaromatic nature of these adducts (Jones et al 1993, Stone et al 1995.…”
Section: Epidemiological and Biological Data On Pahsmentioning
confidence: 99%